Effects of distal robot-assisted therapy combining with task-oriented training on paretic upper extremity functions in clients with sub-acute stroke: A preliminary study - Jitrungruangchai, Pakpoom; Apichai , Sopida; Dhippayom, Jananya Panyamee (Journal of Associated Medical Sciences, 2025)
Background: Robot-assisted therapy (RT) is revolutionizing stroke rehabilitation, offering new hope for improving upper extremity function. When integrated with task-oriented training (TOT), RT has the potential to enhance recovery by promoting more meaningful, functional outcomes for stroke survivors. Despite its promise, evidence on the effectiveness of distal RT combined with TOT remains limited, leaving clinicians and researchers searching for clearer evidence on the best rehabilitation strategies. Objective: This study aimed to investigate the feasibility of distal RT combined with TOT on the function of the paretic upper extremity in sub-acute stroke patients. Materials and methods: This preliminary randomized controlled, assessor-blinded study recruited 15 sub-acute stroke patients. Participants were randomly assigned to either the experimental group (EG; enrolled, N=8; completed, N=7) or the control group (CG; enrolled, N=7; completed, N=7). Both groups received conventional occupational therapy. The EG additionally underwent one hour of distal robot-assisted task-oriented training twice a week for six weeks. Paretic upper extremity function was assessed at baseline and post-rehabilitation using the Fugl-Meyer Assessment for Upper Extremity (FMA-UE) and the Functional Test for Hemiplegic Upper Extremity Thai Version (FTHUE-Thai version). Results: Fourteen patients completed the program. No significant differences in post-intervention mean scores were found between groups. However, change scores were significantly higher in the EG for distal FMA-UE (p=0.002), total FMA-UE (p=0.004), and FTHUE-Thai Version (p=0.026). Additionally, effect size analysis also indicated high effects in the EG for proximal FMA-UE (d=0.94), distal FMA-UE (d=2.28), total FMA-UE (d=1.66), and FTHUE-Thai version scores (d=1.89), suggesting clinically meaningful improvements. Conclusion: Combining distal RT with TOT has the potential to enhance upper extremity function in sub- acute stroke patients. Although further research is needed to confirm these findings, the results are promising for developing more effective rehabilitation strategies.